Association between TIMI Risk Score and in-Hospital Mortality in Acute STEMI Patients Undergoing Primary PCI - Syed Dilbahar Ali Shah, Arshad Ali Shah, Afzal Qasim, Muhammad Sami Khan, Faisal Ahmed, Adnan Wahid, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the association between TIMI risk score and in-hospital mortality and adverse events in acute STEMI patients undergoing primary PCI at a tertiary cardiac care facility. Study design: Retrospective study. Place and duration of study: Catheterization Laboratory of Cardiology Unit, Dr. Ruth KM Pfau, Civil Hospital Karachi from 1st October 2017 to 31st March 2019. Methods: Three hundred and sixty six acute STEMI patients who admitted through emergency and underwent primary angioplasty were enrolled. A proforma was filled out for the said subjects that encompasses continuous and categorical variables including age, gender, family history of coronary artery disease, smoking history, diabetes, hypertension, dyslipidemia, systolic and diastolic blood pressure, heart rate, onset symptoms to emergency room (whether >4 hours or ≤4 h), location of myocardial infarction [anterior, inferior, lateral or posterior, and right ventricular infarction], drugs given prior to angioplasty[aspirin, clopidogrel, prasugrel, heparin, Glycoprotein IIb/IIIa receptor antagonists], success of angiography, culprit vessel, number of diseased vessels, and in-hospital outcomes.. Results: 270 (73.8%) were males and 96 (26.2%) were females with male to female ratio 2.8:1. Mean age was 56.25±11.45 years. Main risk factors were hypertension 230 (62.8%) cases, diabetes 198(54.1%) cases and smoking 167 (45.6%) cases. Onset of symptoms to the arrival to emergency room for treatment was ≤4 hours 201 (54.9%) cases and >4 hours in 165(45.1%) cases. In hospital mortality rate was 3.82%. Hospital in mortality 11(3%) cases was associated with hypertension and diabetes. Conclusion: This study show that a significant number of patients were observed adverse outcomes associated with higher TIMI risk score for in hospital. Therefore, the prognostic TIMI risk score is a powerful tool for predicting hospitalized patients. Key words: Acute myocardial infarction, Coronary artery disease, TIMI Risk Score, In-Hospital Mortality.